PENGARUH PEMANASAN TERHADAP KUALITAS SUSU KAMBING KAYA OMEGA-3 HASIL PEMBERIAN RANSUM YANG MENGANDUNG CAMPURAN GARAM KARBOKSILAT KERING - Yoshi Lia Anggrayni; Rarah Ratih Adjie Maheswari; Bagus Priyo Purwanto (State Islamic University of Sultan Syarif Kasim Riau, 2012)
Nutrition contents of milk was needed for body growth. Milk fat is the main energy source and composed of triglycerides. Essential fatty acids such as EPA and DHA are very important to maintain our health. Therefore, it is commonly fortified into a product in industry. The objective of the research was to study the influence of different heating temperature, fermentation, and churning process to fatty acids content of goat milk produced by goat Etawah with rations containing DCM. The research was divided into two experiments, i.e. 1) influence of giving DCM with different levels to fresh goat milk quality 2) influence of Omega-3-enriched goat milk processing to quality and fatty acids content. The factorial design and complete randomize design were then used in the present study. The treatments were different concentration of DCM in feed (0, 10, 20, 30 g of DCM/kg concentrate) and different of milking time (6 a.m and 6 p.m). Each treatment used three goats. The milk contained highest EPA and DHA resulted from formulation given was heated at different temperatures (LTLT, HTST, and Sterilization). Changes of milk compositions and fatty acid contents were observed. Research on experiment I showed that the production of milk and the quality of fresh goat milk were affected by DCM treatment except protein and acidity degree of milk. Milk from goat milked in the morning contained less fat than in the afternoon. While, milking in the morning increased milk density and milk production. Based on the results of fatty acid content analysis the treatment K-3 (30 g of DCM/kg concentrate) was chosen to do an experiment II. The experiment II results showed that heating treatment did not affect milk quality, except protein and pH. However, fatty acid content of milk was affected by heating treatment. Based on experiment I observation, the best DCM concentration on dairy goats was K-3 and experiment II using HTST treatment on goat milk processing which was able to preserve milk fatty acid contents was recommended based on this research